Arduino wearable projects: design, code, and build exciting wearable projects using Arduino tools - Olsson, Tony (Community Experience Distilled, 2015)
About This BookDevelop an interactive program using sensors and actuators suitable with wearablesUnderstand wearable programming with the help of hands-on projectsExplore different wearable design processes in the Arduino platform and customize them to fit your individual needsWho This Book Is ForThis book is intended for readers who are familiar with the Arduino platform and want to learn more about creating wearable projects. No previous experience in wearables is expected, although a basic knowledge of Arduino will help.